INVESTORS BEHAVIOR IN INDONESIA - Stephanus Rivan Limanjaya; Werner R Murhadi; Endang Ernawati (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
This study aims to describe investor behavior in stock, mutual fund, and bank deposit. The psychology elements that are used in this research are mental accounting, representativeness, familiarity, considering the past, overconfidence, data mining, social interaction, fear and greed, status quo, and emotion. This research uses primary data with a help of questionnaire. The total respondent of this research is 110 people. Data collected by spreading questionnaire manually and online with the help of Google doc. The results showed that most of the respondents give positive respond to all of the elements. The element that has the highest mean value is familiarity element. It means that the respondent think that before they invest in something, they need to know first about that investment.